The predictive and prognostic value of skeletal muscle mass in cancer patients with distant metastases - Cemil Oktay; Gökmen Aktaş; Baran Yusufoğlu; Mahmut Çoraplı; Tülay Kuş (Acta Medica Alanya)
Aim:Skeletal muscle loss is an indicator of cachexia and a strong prognostic factor for some types of cancer. After strict standardization, we aim to evaluate both the predictive and prognostic value of low muscle mass (LMM) in common cancer types for first-line chemotherapy.Methods: This retrospective single-center study was conducted in a regional hospital between 2015 and 2020. Patients diagnosed with distant metastatic cancer were screened and included in the study if they had abdominal computed tomography 45 days prior to first-line chemotherapy. The relationship between LMM and progression-free survival (PFS), overall survival (OS), and objective response rate (ORR) was evaluated.Results: Initially, 289 patients with metastatic cancer were included. The median duration of follow-up was 17 months, with a mean age of 61.09±13.03 years (range 25 to 95), and 45.9% of patients were female. In total, 50.5% of patients had LMM, which was adjusted for gender. LMM was associated with worse OS and PFS in univariate analysis (HR:1.598;1.216-2.100; p=0.001 for OS and HR:1.583;1.216-2.059; p=0.001 for PFS), and this positive association was maintained after adjusted for diagnosis and age. Better ORRs were obtained in respiratory and gastrointestinal tract cancers, breast, prostate and gynecological cancer in non-LMM groups.Conclusion:LMM has not only prognostic value but also predictive value for many types of cancer. Therefore, the assessment of muscle loss should be incorporated as part of the initial routine clinical evaluation.